Entre costumbrismo y novela: Antonio Liñán y Verdugo y Baltasar Mateo Velázquez - Manuel Fernández Nieto (Mélanges de la Casa de Velázquez)
For an analysis of the evolution from the miscellaneous narrative writings of the Golden Age to the novel, with all the peculiar qualities of the genre, the Guía y avisos de forasteros (1620) by Antonio Liñán y Verdugo, and El filósofo del aldea (1626) by Baltasar Mateo Velázquez, are particularly significant. Moreover, it is possible that both works were penned by the same author, Alonso Remón, according to the information assembled here; and they present narrative features ranging from purely costumbrist descriptions to stories that would eventually form the embryo of the novel. The hybrid nature of these works is apparent in the coexistence of dialogues and narratives, fact and fiction or didactics and entertainment. Narration with doctrinal intent, mingled with conversations and classical quotations, was a possible model of literary creation in that it offered writers a new form in which the mixture of elements provided the seed from which the passage of time—and Don Quixote—would eventually produce the modern novel.